Analisis Faktor-Faktor Yang Mempengaruhi Keputusan Investasi Saham Syariah (Pada Perguruan Tinggi Islam Di Kota Medan) - Miswari, Nasma Tia; Rahayu, Sri; Siregar, Wulandari; Suryanitra, Nandika (Prodi Akuntansi, Fakultas Ekonomi, Universitas Hasyim Asy'ari Tebuireng Jombang, 2025)
This study focuses on identifying the influence of financial literacy, risk tolerance, risk perception, and income on Islamic investment decisions of students in the city of Medan. The sample used amounted to 105 respondents. The data for this study were collected using a questionnaire distributed using purposive sampling technique. The statistical method used is the analysis of classical assumptions, multiple linear regression, validity and reliability, and hypothesis using the application in the form of SPSS Statistics 20 software into data processing. Referring to the results obtained from data analysis that financial literacy, risk tolerance, and risk perception have a significant influence on Islamic stock investment decisions. In contrast, income does not have a significant impact on Islamic stock investment decisions.